2019
DOI: 10.3390/ijerph16234725
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Roe Deer Affects the Occurrence of Anaplasma phagocytophilum Ecotypes in Questing Ixodes ricinus in Different Habitat Types of Central Europe

Abstract: The way in which European genetic variants of Anaplasma phagocytophilum circulate in their natural foci and which variants cause disease in humans or livestock remains thus far unclear. Red deer and roe deer are suggested to be reservoirs for some European A. phagocytophilum strains, and Ixodes ricinus is their principal vector. Based on groEL gene sequences, five A. phagocytophilum ecotypes have been identified. Ecotype I is associated with the broadest host range, including strains that cause disease in dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Instead, our results support the idea that parasitization takes place when a larva feeds on a vertebrate. We observed a positive association between infestation with I. hookeri and infection with A. phagocytophilum, which is a pathogen that a I. ricinus larva acquires while feeding on a deer, an A. phagocytophilum-competent host ( Table 2; [47][48][49]). Thus, both acquisition of a bacterium and parasitization by I. hookeri occurs simultaneously.…”
Section: Discussionmentioning
confidence: 91%
“…Instead, our results support the idea that parasitization takes place when a larva feeds on a vertebrate. We observed a positive association between infestation with I. hookeri and infection with A. phagocytophilum, which is a pathogen that a I. ricinus larva acquires while feeding on a deer, an A. phagocytophilum-competent host ( Table 2; [47][48][49]). Thus, both acquisition of a bacterium and parasitization by I. hookeri occurs simultaneously.…”
Section: Discussionmentioning
confidence: 91%
“…In Slovakia it varied from 0.6% up to 30%, with higher prevalence in urban areas than in natural habitats (Pangrácová et al 2013;Derdáková et al 2014;Blaňarová et al 2014;Svitálková et al 2015;Chvostáč et al 2018;Vaculová et al 2019]. It has also been confirmed that the proportion of I. ricinus infected with variants of A. phagocytophilum that are not pathogenic to humans was higher in sites where roe deer were present than in sites with absence of these animals (Hamšíková et al 2019). HGA is not among the communicable diseases in Slovakia.…”
Section: Anaplasma Phagocytophilummentioning
confidence: 94%
“…The latter will be substantially more than the few larvae feeding at the same time with an infected nymph. With regard to differential persistence, a study of A. phagocytophilum Ecotypes in Central Europe did not find less Ecotype II than Ecotype I in questing I. ricinus nymphs originating from a site in the presence of roe deer [ 13 ]. For these reasons, co-feeding and differential persistence were omitted from the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the density of questing I. ricinus infected with A. phagocytophilum (DIN) have partly been attributed to environmental factors such as differences in weather conditions [ 11 , 12 ], habitat characteristics [ 13 ], as well as vertebrate communities [ 14 ]. Whereas small mammals and birds are considered to feed the majority of immature I. ricinus, ungulates act as their main propagation host [ 15 ].…”
Section: Introductionmentioning
confidence: 99%